Sudden cardiac death in athletes: a case review. Issue 2 (20th January 2011) - Kirwan, John; Lundon, Dara; McNeill, B; Ward, Deirdre
Abstract : Introduction: Cardiomyopathies are diseases of the heart muscle. The WHO defined the disorder in 1980 as 'heart muscle disease of unknown cause'.The particular type of cardiomyopathy most connected to sports athletes and to this particular case is that of hypertrophic cardiomyopathy (HCM). HCM is characterised by left and occasionally right ventricular hypertrophy. It is the most prevalent genetic cardiac abnomality, affecting at least 1:500 of the adult population in the absence of aortic valve disease or systemic hypertension. In approximately 60–70% of patients, HCM is caused by mutations in the sacromeric contractile protein genes and is transmitted via an autosomal dominant trait with incomplete penetrance, the most common mutations being in the β-myosin heavy chain and the cardiac myosin-binding protein C genes. The incidence of SCD in professional ethletes is actually quite low, estimated to be between 1/50 000 to 1/300 000 athletes over a 10–20 year period however the incidence among non-professional athletes partaking in high intensity activities is significantly higher. I hope that this particular case, which is an extreme in its example would high the dilema that exists in modern non-professional sporting bodies, in particular in Ireland and the need to address the need for screenind to prevent such deaths occuring in athletes. Case: This 47-year-old man initially presented to casualty in 2007 with a profound presyncopal episode. This particular episode was not associated with exertion however on taking his history, it was noted that his younger brother had died suddenly in the 80's while playing a hurling match. Subsequently, a number of years later, this gentlemans brother was diagnosed with a cardiomyopathy and was being worked-up for a transplant when he also died suddenly. His father also died suddenly in his early 70's with post mortem revealing a cardiomyopathy. Wth such a history and presenting symptoms, a major cardiac work-up was undertaken including the implantation of a loop recorder for 13 months which revealed numerous salvos of non-sustained VT, a coronory angiogram which failed to show any ischaemic disease, multiple stress testing, a cardic MRI which revealed significant myocardial fibrosis and cardiac genetic testing for query arrhythmogenic right ventricular cardiomyopathy/hypertrophic cardiomyopathy, the results of which are awaited. This gentleman was initially assessed by a cardiologist in 2008 and at by the time this assessment hasd been performed, he was been treated with antiarrhytmic medication and the advise of exercise intensity reduction to very mild levels were given. He managed with this treatment for a period of time, however in March of this year was admitted with another presyncopal episode, at which point the decision to put a intracardiac device was made. This case exhibits the extreme of what is a relatively common genetic disorder of otherwise young healthy adults. The media has well advertised the more high profile cases in Ireland in recent years however the dilema that now exists is should there be an incentive for all sporting bodies to initiate screening programs for these disorders prior to athletic participation, and hence attempt to avoid sad and disastrous cases like that of this gentleman and his famly.